Isolation And Identification Of New Lipolytic Thermophilic Bacteria From An Indian Hot Spring - BISHT, S.P.S; AMRITA KUMARI PANDA (International Journal of Pharma and Bio Sciences, 2011)
Thermophilic lipase producing bacteria have been isolated and characterized from an Indian hot spring, isolates named as AK-P1, AK-P2 and AK-P3 respectively. The strain AK-P2 was first of its kind with reference to its lipase producing potential. The phylogenetic analysis of these strains using 16S rDNA sequence data revealed that the strain AK-P1 had highest homology (100%) with Acinetobacter sp. 01B0;, AK-P2 had highest homology (99.9%) with Brevibacillus borstelensis; AR9 and AK-P3 have shown 99.2 % similarities with Porphyrobacter cryptus (T); ALC-2. Maximal lipase production by AK-P2 was observed at the end of the stationary phase (36 h). The optimum temperature and pH for this crude enzyme activity was 60ºC and 10.0 respectively. Enzyme extracted from AK-P2 exhibited a Km 0.052mM and Vmax 0.645 μM/min/ml with p-nitrophenyl laurate as a substrate.